Antibacterial and anti-biofilm activities of peppermint essential oil against Staphylococcus aureus. (March 2019) - Kang, Jiamu; Jin, Wenyuan; Wang, Jingfan; Sun, Yuyang; Wu, Xiaoxia; Liu, Liu
Abstract: Peppermint essential oil (PEO) has been reported to prevent microbial growth and prolong the shelf-life of food, but there are few studies about its possible antibacterial mechanism and anti-biofilm activity against Staphylococcus aureus ( S. aureus ). In this study, the antibacterial mechanism of PEO on planktonic S. aureus was investigated by determining electrical conductivity, cell membrane integrity, cell viability, and bacterial morphology. Moreover, a crystal violet quantification assay and plate colony counts were used to evaluate the effects of PEO on inhibiting and inactivating S. aureus biofilms. The results show that PEO affected the permeability and integrity of the S. aureus cell membrane, as evidenced by the increase in relative electrical conductivity and leakage of nucleic acids, proteins, and ATP. Decreased cell viability and changes in cell morphology further confirmed the cell membrane damage to S. aureus by PEO. In addition, PEO significantly inhibited the formation of biofilm, and inactivated mature biofilm formed by S. aureus . These findings suggest that PEO has the potential to control planktonic S. aureus and its biofilm in food processing environments. Highlights: Peppermint essential oil (PEO) can damage the cell membrane of S. aureus. PEO had potent inhibitory effect on S. aureus biofilm formation. PEO inactivated and removed the mature biofilm formed by S. aureus.